2016
DOI: 10.1128/aem.01235-16
|View full text |Cite
|
Sign up to set email alerts
|

The Microbiota of Breast Tissue and Its Association with Breast Cancer

Abstract: In the United States, 1 in 8 women will be diagnosed with breast cancer in her lifetime. Along with genetics, the environment contributes to disease development, but what these exact environmental factors are remains unknown. We have previously shown that breast tissue is not sterile but contains a diverse population of bacteria. We thus believe that the host's local microbiome could be modulating the risk of breast cancer development. Using 16S rRNA amplicon sequencing, we show that bacterial profiles differ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
437
1
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 430 publications
(470 citation statements)
references
References 49 publications
23
437
1
9
Order By: Relevance
“…In cancer patients, adjacent histologically normal and non-cancer samples showed no significantly differences in Shannon diversity index or number of observed OTUs. These data are consistent with Urbaniak et al’s findings [67] but disagree with those of Xuan et al [44]. Nevertheless, cancer patient breast tissue microbiota clustered significantly differently from non-cancer patients ( p = 0.03), mainly due to the fact that breast tissue in cancer patients exhibited a significantly decreased relative abundance of Methylobacterium (while this was increased at the site of the tumor in the study of Xuan et al [44]; median 0.10 vs. 0.24, p = 0.03).…”
Section: Mammary Microbiota and Breast Cancersupporting
confidence: 94%
“…In cancer patients, adjacent histologically normal and non-cancer samples showed no significantly differences in Shannon diversity index or number of observed OTUs. These data are consistent with Urbaniak et al’s findings [67] but disagree with those of Xuan et al [44]. Nevertheless, cancer patient breast tissue microbiota clustered significantly differently from non-cancer patients ( p = 0.03), mainly due to the fact that breast tissue in cancer patients exhibited a significantly decreased relative abundance of Methylobacterium (while this was increased at the site of the tumor in the study of Xuan et al [44]; median 0.10 vs. 0.24, p = 0.03).…”
Section: Mammary Microbiota and Breast Cancersupporting
confidence: 94%
“…Hypothesizing that species more accustomed to causing disease and carcinogenic reactions might be present and associated with breast cancer, we conducted 2 studies. We were the first to describe a breast microbiome and demonstrate the differences in the breast microbiome between women with cancer and those who are healthy, suggesting a breast microbiome may indeed have some protective properties (Urbaniak et al 2014(Urbaniak et al , 2016b. While not proving cause and effect, the discoveries could open a new line of investigation into "environmental" factors inducing cancer, and a new method to modify this microbiome to one associated with health.…”
Section: Extending the Translation To Women's Healthmentioning
confidence: 99%
“…In hospital settings, recognition of the value of beneficial microbes is happening, with use of probiotics to reduce mortality and morbidity of low-birth-weight premature babies (Sawh et al 2016) (including in London, Ontario, after 10 years of advocating) and to prevent antibiotic-associated diarrhea including Clostridium difficile infections (Hickson et al 2007;Maziade et al 2015), albeit not all studies have shown efficacy (Allen et al 2013). The success of fecal microbiota transplant in curing C. difficile infections further emphasizes the impact of beneficial microbes (van Nood et al 2013). However, this use is far from universal, in part because some clinicians are not convinced, products may not be available, or administrators are concerned with law suits.…”
Section: The Futurementioning
confidence: 99%
“…Although results of their analysis were different from ours, some interesting studies may offer support for certain envi ronmental factors being associated with an increased incidence of breast cancer [36,37] . Urbaniak et al demonstrated that breast tissue contains a diverse population of bacteria [38,39] . Using the analysis of 16S rRNA, they showed that the pattern of microbiome is completely different between the adjacent normal breast tissue from women with breast cancer and breast tissue from healthy controls.…”
Section: Breast Cancermentioning
confidence: 99%